Tradisi Pager Gesek dalam Sedekah Bumi - Qomaria, Elysa Nurul; Fatikah, Noor (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The research aims to analyze the pager gesek tradition in the sedekah bumi ceremony of Srikandang Village, as well as the Islamic values integrated within it. The research method used is descriptive qualitative, with data collected through observation, interviews, and literature review. The findings show that the pager gesek tradition is not just an annual ritual but also a representation of religious values and local wisdom that strengthens social harmony. The study also reveals that this tradition enhances social solidarity and serves as an expression of gratitude to God for the blessings of nature, while preserving the village's cultural identity. The discussion highlights the role of this tradition in promoting harmony by integrating religious values and local practices. The conclusion emphasizes that the tradition fosters mutual respect, cultural sustainability, and unity within the community.